2017
DOI: 10.1363/psrh.12015
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Incidence and Service Availability In the United States, 2014

Abstract: CONTEXT National and state-level information about abortion incidence can help inform policies and programs intended to reduce levels of unintended pregnancy. METHODS In 2015–2016, all U.S. facilities known or expected to have provided abortion services in 2013 or 2014 were surveyed. Data on the number of abortions were combined with population data to estimate national and state-level abortion rates. The number of abortion-providing facilities and changes since a similar 2011 survey were also assessed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
229
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 368 publications
(235 citation statements)
references
References 14 publications
4
229
0
2
Order By: Relevance
“…We identified almost 800 abortion facilities, which is consistent with other estimates of abortion clinics and nonspecialized clinics providing abortion [1] but we found that these facilities are not distributed proportionately by population. Access to transportation is a barrier for people seeking all types of healthcare, in both urban and rural settings [26].…”
Section: Abortion Desertssupporting
confidence: 88%
See 4 more Smart Citations
“…We identified almost 800 abortion facilities, which is consistent with other estimates of abortion clinics and nonspecialized clinics providing abortion [1] but we found that these facilities are not distributed proportionately by population. Access to transportation is a barrier for people seeking all types of healthcare, in both urban and rural settings [26].…”
Section: Abortion Desertssupporting
confidence: 88%
“…The high proportion of facilities offering only medication abortion reflects the opportunities provided by medication abortion: the skills required for clinicians to provide it are minimal (compared with aspiration or surgical abortion), the large majority of abortions in the United States (80.5%) occur at or before 10 weeks gestation (the current accepted limit by which medication abortion can be provided) [30], and the demand has increased with the proportion of women choosing this method now accounting for 31% of non-hospital abortions (compared to 6% in 2001) [1]. Additionally, states in the Northeast and West are less likely to have laws that limit the provision of medication abortion to physicians [31] and more likely to have policies that allow nurse practitioners, certified nurse midwives, and physicians assistants to offer medication abortion as part of their scope of practice.…”
Section: Abortion Desertsmentioning
confidence: 99%
See 3 more Smart Citations